2017
DOI: 10.22631/rr.2017.69997.1013
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin (OPG) levels, total soluble receptor activator of nuclear factor-Kappa B ligand (total sRANKL) , and RANKL/OPG ratio in patients with rheumatoid arteritis

Abstract: Background: Rheumatoid arthritis (RA) is one of most important collagen vascular diseases. It has an unknown origin. Objectives: The aim of this study was to evaluate circulating levels of osteoprotegerin (OPG), total soluble receptor activator of nuclear factor-Kappa B ligand (total sRANKL), and OPG/RANKL ratio in patients with RA. Methods: Forty-five females with RA, who fulfilled the American college of rheumatology (ACR) criteria for RA were included in this cross-sectional study. The overall disease activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This could be due to the small number of RA patients (26 patients) and the healthy group (N=10) in his study 19 . Sousan et al study in Iran 2017 did not find a statistically significant difference (P=0,49) in serum RANKL levels between patients and healthy controls because all of their patients and controls were only women 37 . Our result also contrasted with the Carmen study et al 2016 in Spain, which showed that serum RANKL values were below the detection limit in 85% of studied RA patients (N=93).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This could be due to the small number of RA patients (26 patients) and the healthy group (N=10) in his study 19 . Sousan et al study in Iran 2017 did not find a statistically significant difference (P=0,49) in serum RANKL levels between patients and healthy controls because all of their patients and controls were only women 37 . Our result also contrasted with the Carmen study et al 2016 in Spain, which showed that serum RANKL values were below the detection limit in 85% of studied RA patients (N=93).…”
Section: Discussionmentioning
confidence: 92%
“…These studies and ours confirm that increased RANKL level may reflect RA activity and may be added with DAS28 as an assistant biomarker to assess disease activity . On the other hand, Kolahi et al study in Iran 201742 and Boman et al study in Sweden 2017 did not observe a correlation between serum RANKL levels and DAS28 in patients with RA 19 . According to the correcation with CRP, a study by Bruno et al study 2021 in Italy 44 and Burska et al 2021 study in the United States did not find a significant association between serum RANKL and CRP 45 .…”
mentioning
confidence: 91%